ENGLISH COURSE ENROLMENT ON STUDENTS’ SPEAKING PROFICIENCY: A PERCEPTION-BASED STUDY - Syahrul Jihad; Ika Lestari Damayanti (ELTIN Journal, 2024)
English is considered as a foreign language in Indonesia, the EFL learners face difficulties in speaking due to lack of practice and experience conveying their opinion, feeling, thought, and message in the target language because they have limited time and place to utilize it. There are numerous ways that can support students to enhance their speaking ability, one of them are joining an English course. This study aims to find out about students’ perception of English course can assist them to improve their speaking skill. Two students who have been learning English at the course were involved in this study. A qualitative design was used, and semi-structured interview was conducted to obtain the data. The results indicate that English course improves students’ speaking ability and enhance their public speaking skill. Some suggestions are suggested to enhance the quality of the students’ speaking skill and develop more engaging and challenging activity to the English course.